Risk factors and treatment approaches to seasonal affective disorder: a review - Jurgaitytė , V.; Khawaja , N.; Dijokas , J.; Rimkevičiūtė , P. (Neurologijos seminarai, 2020)
Seasonal Affective Disorder (SAD) is a type of depression which emerges seasonally, in winter or summer. This condition affects 1-2% of the general population; however, in regions more than 30 degrees of the equator, a higher proportion (10-20%) of people suffer from SAD. There is a milder form of SAD, subsyndromal SAD (S-SAD), which is known as “winter blues”. Besides environmental risk factors, such as day length and sunlight exposure, genetics and neurochemical changes in the brain also play a role in SAD patients showing that this disorder is heterogeneous. Imbalances in the circadian rhythm and dysregulation of neurotransmitters (serotonin, dopamine, and norepinephrine) have been identified as risk factors for symptomatic SAD. SAD symptoms can be diminished by bright light therapy, regulating patients’ circadian rhythms, and cognitive-behavioural therapy, which more indirectly focuses on alleviating depressive symptoms by allowing patients to actively manage how they perceive stress and anxiety. The paper compares effectiveness and safety of treatment methods against SAD.
Keywords: seasonal affective disorder; seasonal depression; subsyndromal seasonal affective disorder; bright light therapy; cognitive behavioural therapy